Validación de un software para el cálculo del balance hídrico en cuencas hidrográficas - Romero Camacho, Héctor Alejandro (2018)
Abstract:The present work of end of titration shows the validation of the BaWare software, which was developed by programming with modules in the PYTHON language and calculates the water balance by means of temperature and precipitation data obtained from meteorological stations, and the characteristics of latitude and area. The calibration of the water balance obtained uses parameters whose values are defined for each basin by the software. The validation is done by collecting data from several basins with different characteristics and after obtaining the results, the effectiveness of the program is determined, comparing the values of the correlation indexes of the objective functions. Using BaWare, better results were obtained when the area of the basin was 462 km2, this being the smallest area; the basin is located in mid-latitudes where extreme climates do not occur; the data entered are homogeneous and the values used in the calibration parameters have 4 or more decimals.